Case Report: Disseminated leishmaniasis and rheumatoid arthritis: navigating a clinical conundrum - Shahini, Endrit; Marziliano, Donatello; Losito, Francesco; Zappimbulso, Marianna; Cavalcanti, Elisabetta; Armentano, Raffaele; Fucilli, Fabio; Cozzolongo, Raffaele; Ingravallo, Giuseppe; Pappagallo, Fabrizio; Iatta, Roberta; Desantis, Vanessa; et al. (Frontiers in Immunology, 2025)
BackgroundLeishmaniasis is a potentially life-threatening protozoan infection that presents with many clinical manifestations, including cutaneous, mucocutaneus and visceral forms. In patients with rheumatoid arthritis (RA), cutaneous leishmaniasis can persist or re-emerge due to treatment-induced immunosuppression. However, it remains unclear whether this severe opportunistic infection is primarily driven by medication-induced immunosuppression or other poorly understood immune-mediated mechanisms that increase susceptibility.Case presentationWe describe an unusual case of disseminated leishmaniasis in a 50-year-old Italian man from Apulia, diagnosed with RA two years earlier. Following 15 months of unsuccessful immunosuppressive therapies, he developed severe multilineage pancytopenia, moderate hypertransaminasemia, elevated inflammatory markers, monoclonal gammopathy, clinically significant hepatosplenomegaly, and an ulcerated skin lesion. Initial diagnostic efforts excluded common infectious agents, primary hematological disorders, Felty syndrome, and amyloidosis. The non-specific histopathological findings from the pyoderma gangrenosum-like lesion and the transient clinical response to empirical steroids, broad-spectrum antibiotics, and granulocyte colony-stimulating factors further complicated the diagnostic process. The breakthrough came when a liver biopsy, performed to investigate persistent hypertransaminasemia, revealed Leishmania amastigotes within macrophages. This finding triggered a re-evaluation of the ulcerated skin lesion, and histological analysis confirmed concurrent cutaneous leishmaniasis. Subsequent bone marrow biopsy also identified Leishmania amastigotes, clinching the diagnosis of disseminated leishmaniasis. A holistic re-assessment of the patient’s clinical presentation, developmental history, and laboratory, radiologic, and pathological data led to the definitive diagnosis. Treatment with standard intravenous amphotericin B resulted in clinical resolution. A follow-up bone marrow biopsy a few weeks later confirmed the infection had been completely eradicated.ConclusionsIn patients with rheumatological conditions, the overlapping symptoms of systemic diseases and infections like leishmaniasis can lead to significant diagnostic delays. This case underscores the importance of comprehensive and meticulous diagnostic evaluations in immunosuppressed individuals to prevent potentially fatal outcomes.